ANALISIS HIDROKIMIA DALAM PENENTUAN TIPE DAN GOLONGAN FLUIDA GEOTERMAL SULILI KABUPATEN PINRANG SULAWESI-SELATAN - Emi Prasetyawati Umar; Muhamad Hardin Wakila; Jamal Rauf Husain; Jamaluddin Jamaluddin; Syamsuddin Syamsuddin; Rizky Nurul Aulia (Institut Teknologi Sepuluh Nopember, 2022)
Field surveys in the Sulili Region show geothermal characteristics in the form of manifestations, namely hot water springs. This study aims to determine the type of geothermal fluid in the study area based on the Na-K-Mg geothermometer method and then classify it based on trilinear and ternary diagrams. The results showed that the types of hot springs from the three hot springs in the study area were included in the chloride type with a percentage between 96.209% -96.651% which was plotted on the trilinear diagram. Based on the ternary diagram plotting, the geothermal fluid in the study area belongs to the immature water group. Based on the results of the study it can be concluded that the type of hot water springs in the study area is chloride with one of the hot springs included in the immature water group, namely EPU-1 hot water spring station, while two hot water spring stations, such as EPU-2 and EPU-3 stations cannot plotted due to the high levels of Mg at that station.